2015
DOI: 10.1590/s0100-736x2015000700002
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of fetal bovine serum alters histone modification H3R26me2 during preimplantation development of in vitro produced bovine embryos

Abstract: In vitro production (IVP) of bovine embryos is not only of great economic importance to the cattle industry, but is also an important model for studying embryo development. The aim of this study was to evaluate the histone modification, H3R26me2 during pre-implantation development of IVP bovine embryos cultured with or without serum supplementation and how these in vitro treatments compared to in vivo embryos at the morula stage. After in vitro maturation and fertilization, bovine embryos were cultured with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The percentages of BLs development and the total cell number per BL were significantly increased in the medium supplemented with FBS. Similar results were found in IFV porcine embryo development where 10% FBS was added in the chemically defined medium [ 19 ], and also 2.5% FBS was used for IVF bovine embryo production [ 20 ]. However, it was found that 5% FBS has been advantageous during the pre-cleavage stage, and 10%–20% FBS has been advantageous during the post-cleavage stage of the bovine embryos and also overcomes the deleterious effects of serum on early developing embryos by exploiting embryotrophic effects during later stage [ 21 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The percentages of BLs development and the total cell number per BL were significantly increased in the medium supplemented with FBS. Similar results were found in IFV porcine embryo development where 10% FBS was added in the chemically defined medium [ 19 ], and also 2.5% FBS was used for IVF bovine embryo production [ 20 ]. However, it was found that 5% FBS has been advantageous during the pre-cleavage stage, and 10%–20% FBS has been advantageous during the post-cleavage stage of the bovine embryos and also overcomes the deleterious effects of serum on early developing embryos by exploiting embryotrophic effects during later stage [ 21 ].…”
Section: Discussionsupporting
confidence: 69%
“…Another study on bovine embryo culture indicated that adding FBS in the culture medium promoted development to the morula and BL stage [ 20 ]. Mostly, FBS acts as a protein source in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation